Improving health literacy and treatment understanding of hidradenitis suppurativa using group educational interventions. (3rd October 2019) - Prussick, Lisa; Tonelli, Sarah; Gottlieb, Alice B.; Joshipura, Deep; Alomran, Abdulaziz; Zancanaro, Pedro; Courtney Kachuk, RN; Dumont, Nicole; Rosmarin, David
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic immune-mediated skin disorder characterized by inflamed, painful abscesses most commonly located in the intertriginous regions that may lead to significant scarring and social stigma. It is unclear how much patients with HS understand about their disease. Objective: We sought to evaluate baseline knowledge of patients who have HS, as well as to evaluate if an educational intervention of a teaching session about the disease will help increase patient's knowledge of their ailment and treatment options. These sessions also act as a support group for the participants, during which they have time to connect with one another and discuss their experiences with HS. Methods: Participants were recruited at Tufts Medical Center by searching for an ICD-10 code of HS or were identified via advertisement. Eligible subjects were given a study specific questionnaire pre- and post an educational lecture on HS. Results: Twenty subjects participated in the study, conducted from June 2017 through January 2018. Mean test score improved from 62.7% to 82.7% ( p  < .0001). Additionally, participants reported an average of 20.3% ( p = .0002) improvement in their knowledge of HS postintervention. Conclusions : Group information sessions can be an effective means to educate patients with hidradenitis suppurativa and were preferable to the majority of participants in this study.